Artificial Intelligence: Opportunities and Threats in Islamic Higher Education - Alhajj, Irfan Qowwiyul Aziz; Budiman , Budiman; Karolina , Asri; Apriani , Eka; Warlizasusi, Jumira; Kurniawan, Kurniawan (Mudir : Jurnal Manajemen Pendidikan, 2024)
AI, or Artificial Intelligence, is a technology developed to perform tasks that typically require human intelligence. The use of AI remains a hot topic in both developed and developing countries as the technology continues to advance. AI is considered to have significant potential in revolutionizing the education sector due to its ability to provide more personalized learning experiences. However, the emergence of AI also raises various concerns about the potential threats it poses to the education system. This research aims to further discuss the opportunities and threats of using AI in learning within Islamic higher education. This study employs a qualitative research method as it seeks to understand and describe the phenomena related to its research subjects. A phenomenological approach is used, focusing on the essence of the data, which is factual and based on the experiences of the research subjects, or the invariant structure, which pertains to how the subjects interpret their experiences. The research was conducted at the State Islamic Institute of Curup, and the subjects included students, lecturers, and administrative staff at the institute. Data were collected through interviews and observations and were processed and analyzed using data triangulation techniques. The results of this study indicate that AI holds great potential for Islamic higher education in both the educational and administrative fields. In education, AI can enhance the efficiency of learning, while in administration, AI can simplify tasks and boost the productivity of educational staff. Alongside these significant opportunities, AI also brings threats. The emergence of laziness, the tendency to take tasks lightly, and dependence on AI are major concerns in its usage. Additionally, automation in administration poses a threat to the need for administrative staff, as their roles may be replaced by AI.